Aqueous black rice (Oryza sativa L. indica) extract enhanced the activation of CD4+ and CD8+ T cells in mouse breast cancer model - Fadjar Kurnia Hartati; Wirdatun Nafisah; Adi Sutanto; Elfi Anis Saati; Miftahul Khairoh; Sjamsiah (Pensoft Publishers, 2024)
Black rice is a functional food of Indonesia that has several pharmaceutical activities including anti-cancer. This study aimed to evaluate the immunomodulatory potential of aqueous black rice (ABR) extract on mouse breast cancer model. A carcinogen, 7,12-dimethylbenz[a]anthracene (DMBA), was applied for breast cancer induction in mice. The study was designed to be seven groups (six mice in each group), including Normal or control group (N), a Cancer (C; DMBA-induced mice) group, Cisplatin (Cis; DMBA-induced mice + Cisplatin) treatment group, and DMBA-induced mice + ABR extract (ABR1; dose 1 or 0.2 g/kg, ABR2; dose 2 or 0.3 g/kg, ABR3; dose 3 or 0.4 g/kg, and ABR4; dose 4 or 0.5 g/kg) treatment group. The cancer-bearing mice were given ABR extract for two weeks, and flow cytometry was used to assess the numbers of CD4+ and CD8+ T cells, as well as the production of inflammatory cytokines IL-17, TNFα, and IFNγ. The histopathology of breast tissue in mice was analyzed using hematoxylin and eosin staining and microscope observation. The induction of DMBA in mice lower the activation of CD4+ and CD8+ T cells, and induced IL-17, TNFα, and IFNγ production. The histology of the mammary tissue of the untreated mice demonstrated an infiltration of cancer cells toward stroma, whereas that of the treated groups, especially those under high doses of ABR extract, showed a better prognosis, exhibiting a reduction in cancer cells surrounded by a relatively larger number of adipose tissues. The activation of CD4+ and CD8+ T cells, as well as the reduction of cytokines (IL-17, TNFα, and IFNγ), were thought to be influenced by ABR extract. The activation of T cells optimized the elimination of cancer cells activity; moreover, the production of pro-tumor cytokines was inhibited.